New polymer-graphene nanocomposite electrodes with platinum-palladium nanoparticles for chemical power sources - N. A. Yashtulov; M. V. Lebedeva; L. N. Patrikeev; N. K. Zaitcev (eXPRESS Polymer Letters)
In the present experimental work new polymer-reduced graphene oxide (rGO) nanocomposites with bimetallic platinum-palladium nanoparticles as functional electrodes for chemical power sources were prepared. The size and shape of nanoparticles in the composites have been studied by use of atomic force and high-resolution transmission electron microscopy techniques, X-ray phase analysis and small-angle X-ray scattering. Model tests on the basis of chemically-obtained composite electrodes under operating conditions of fuel elements with formic acid oxidation were carried out.